Influence of learning media based on adobe flash professional to psychomotor domain learning outcomes on plc courses viewed from level of creative thinking student - Supari Muslim; Nahindi Putra Gitama; Bambang Suprianto; Erina Rahmadyanti; Nita Kusumawati (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2018)
This study uses adobe flash professional based learning media for experimental class while in control class using CourseLab media. Learning media based on adobe flash professional designed in the form of applications for smartphones and computers or notebooks. This study aims to determine the interaction and differences in learning result for students who have low and high creative thinking level who learn by using adobe flash professional media than students who use the media CourseLab. This research was conducted in department D3 mechatronic class of 2015 at State University of Trunojoyo Madura (UTM) on PLC course and using factorial design 2 x 2, with total of students in the experimental class as much as 44 people and total of students in the control class as many as 26 people. Data Processing Technique for hypothesis testing, used two-independent-samples test technique. If the prerequisite test of normality and homogeneity is not met, we will use the mann-whitney u test technique. Research finds: (1) for students who have a low level of creative thinking, who learn by using adobe flash professional learning media, psychomotor domain learning outcomes is significantly higher than students who learn by using instructional media CourseLab; (2) for students who have a high level of creative thinking, who learn by using adobe flash professional learning media, psychomotor domain learning outcomes is significantly higher than students who learn by using instructional media CourseLab; and (3) there is a significant interaction between the level of students' creative thinking and learning media, to psychomotor domain learning outcomes. Research suggests: (1) research subjects used at least more than 150 students, to obtain better data (normal distributed data); and (2) the preparation of tools and materials must be in accordance with the needs to be used, so that the quality of learning is increasing.